-4*(5-x)+(3-x)*(4-x)*(5-X)-4*(3-X)=0

Simple and best practice solution for -4*(5-x)+(3-x)*(4-x)*(5-X)-4*(3-X)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -4*(5-x)+(3-x)*(4-x)*(5-X)-4*(3-X)=0 equation:


Simplifying
-4(5 + -1x) + (3 + -1x)(4 + -1x)(5 + -1X) + -4(3 + -1X) = 0
(5 * -4 + -1x * -4) + (3 + -1x)(4 + -1x)(5 + -1X) + -4(3 + -1X) = 0
(-20 + 4x) + (3 + -1x)(4 + -1x)(5 + -1X) + -4(3 + -1X) = 0

Multiply (3 + -1x) * (4 + -1x)
-20 + 4x + (3(4 + -1x) + -1x * (4 + -1x))(5 + -1X) + -4(3 + -1X) = 0
-20 + 4x + ((4 * 3 + -1x * 3) + -1x * (4 + -1x))(5 + -1X) + -4(3 + -1X) = 0
-20 + 4x + ((12 + -3x) + -1x * (4 + -1x))(5 + -1X) + -4(3 + -1X) = 0
-20 + 4x + (12 + -3x + (4 * -1x + -1x * -1x))(5 + -1X) + -4(3 + -1X) = 0
-20 + 4x + (12 + -3x + (-4x + 1x2))(5 + -1X) + -4(3 + -1X) = 0

Combine like terms: -3x + -4x = -7x
-20 + 4x + (12 + -7x + 1x2)(5 + -1X) + -4(3 + -1X) = 0

Multiply (12 + -7x + 1x2) * (5 + -1X)
-20 + 4x + (12(5 + -1X) + -7x * (5 + -1X) + 1x2 * (5 + -1X)) + -4(3 + -1X) = 0
-20 + 4x + ((5 * 12 + -1X * 12) + -7x * (5 + -1X) + 1x2 * (5 + -1X)) + -4(3 + -1X) = 0
-20 + 4x + ((60 + -12X) + -7x * (5 + -1X) + 1x2 * (5 + -1X)) + -4(3 + -1X) = 0
-20 + 4x + (60 + -12X + (5 * -7x + -1X * -7x) + 1x2 * (5 + -1X)) + -4(3 + -1X) = 0
-20 + 4x + (60 + -12X + (-35x + 7xX) + 1x2 * (5 + -1X)) + -4(3 + -1X) = 0
-20 + 4x + (60 + -12X + -35x + 7xX + (5 * 1x2 + -1X * 1x2)) + -4(3 + -1X) = 0
-20 + 4x + (60 + -12X + -35x + 7xX + (5x2 + -1x2X)) + -4(3 + -1X) = 0
-20 + 4x + (60 + -12X + -35x + 7xX + 5x2 + -1x2X) + -4(3 + -1X) = 0
-20 + 4x + 60 + -12X + -35x + 7xX + 5x2 + -1x2X + (3 * -4 + -1X * -4) = 0
-20 + 4x + 60 + -12X + -35x + 7xX + 5x2 + -1x2X + (-12 + 4X) = 0

Reorder the terms:
-20 + 60 + -12 + -12X + 4X + 4x + -35x + 7xX + 5x2 + -1x2X = 0

Combine like terms: -20 + 60 = 40
40 + -12 + -12X + 4X + 4x + -35x + 7xX + 5x2 + -1x2X = 0

Combine like terms: 40 + -12 = 28
28 + -12X + 4X + 4x + -35x + 7xX + 5x2 + -1x2X = 0

Combine like terms: -12X + 4X = -8X
28 + -8X + 4x + -35x + 7xX + 5x2 + -1x2X = 0

Combine like terms: 4x + -35x = -31x
28 + -8X + -31x + 7xX + 5x2 + -1x2X = 0

Solving
28 + -8X + -31x + 7xX + 5x2 + -1x2X = 0

Solving for variable 'X'.

Move all terms containing X to the left, all other terms to the right.

Add '-28' to each side of the equation.
28 + -8X + -31x + 7xX + 5x2 + -28 + -1x2X = 0 + -28

Reorder the terms:
28 + -28 + -8X + -31x + 7xX + 5x2 + -1x2X = 0 + -28

Combine like terms: 28 + -28 = 0
0 + -8X + -31x + 7xX + 5x2 + -1x2X = 0 + -28
-8X + -31x + 7xX + 5x2 + -1x2X = 0 + -28

Combine like terms: 0 + -28 = -28
-8X + -31x + 7xX + 5x2 + -1x2X = -28

Add '31x' to each side of the equation.
-8X + -31x + 7xX + 5x2 + 31x + -1x2X = -28 + 31x

Reorder the terms:
-8X + -31x + 31x + 7xX + 5x2 + -1x2X = -28 + 31x

Combine like terms: -31x + 31x = 0
-8X + 0 + 7xX + 5x2 + -1x2X = -28 + 31x
-8X + 7xX + 5x2 + -1x2X = -28 + 31x

Add '-5x2' to each side of the equation.
-8X + 7xX + 5x2 + -5x2 + -1x2X = -28 + 31x + -5x2

Combine like terms: 5x2 + -5x2 = 0
-8X + 7xX + 0 + -1x2X = -28 + 31x + -5x2
-8X + 7xX + -1x2X = -28 + 31x + -5x2

Reorder the terms:
28 + -8X + -31x + 7xX + 5x2 + -1x2X = -28 + 31x + -5x2 + 28 + -31x + 5x2

Reorder the terms:
28 + -8X + -31x + 7xX + 5x2 + -1x2X = -28 + 28 + 31x + -31x + -5x2 + 5x2

Combine like terms: -28 + 28 = 0
28 + -8X + -31x + 7xX + 5x2 + -1x2X = 0 + 31x + -31x + -5x2 + 5x2
28 + -8X + -31x + 7xX + 5x2 + -1x2X = 31x + -31x + -5x2 + 5x2

Combine like terms: 31x + -31x = 0
28 + -8X + -31x + 7xX + 5x2 + -1x2X = 0 + -5x2 + 5x2
28 + -8X + -31x + 7xX + 5x2 + -1x2X = -5x2 + 5x2

Combine like terms: -5x2 + 5x2 = 0
28 + -8X + -31x + 7xX + 5x2 + -1x2X = 0

The solution to this equation could not be determined.

See similar equations:

| 3x-6(6x-15)=-9 | | 5+x=-10+7 | | -4(5-x)+(3-x)(4-x)(5-X)-4(3-X)=0 | | -3.3x=-29.7 | | -182=6x-4(3x+29) | | ft(-4)=3x^2+7 | | 3-2(2x-4)=3x-4 | | x+.15x=1500 | | 0.6+7.9=4.6 | | f(x)=3x^2+7 | | 8x^2-53-21=0 | | 15x^2+25xy-45xz=0 | | x+x+23+23= | | 8a+5b=44 | | 4x+24=23 | | -5x+3(-6x+8)=-252 | | 10msquared= | | 3(2-3x)=2(-4x+7) | | exp(-0.1X^2)= | | 9/10-4/10= | | 2/5(x-9/40=3/10(7-2x) | | 2p+x+4p= | | 6x-(7+4x)= | | a^2(b-4)-25(b-4)=0 | | z=3x+9y | | -6y+x=5 | | 5/7x8/15 | | Y-6=-4(x+7) | | N^2-14n+69=-8 | | Ln(5x-8)=1 | | x=6x+5 | | 4x+37=100 |

Equations solver categories